2019
DOI: 10.2147/cmar.s232219
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prediction of Overall Survival of Patients with Completely Resected Non-Small Cell Lung Cancer: Analyses of Preoperative Spirometry, Preoperative Blood Tests, and Other Clinicopathological Data</p>

Abstract: PurposeRisk stratification of patients with non-small cell lung cancer (NSCLC) is crucial to select the appropriate treatments, but available models for patients with complete resection are unsatisfactory. The purpose of this study was to determine a prediction model based on clinical information, routine physical and blood tests, and molecular markers.Patients and MethodsThis was a retrospective cohort study of patients who underwent surgical resection for lung cancer between 2009 to 2013. Potential prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The PLR was demonstrated to be an independent predictor of diabetes with chronic complications [38][39][40] and tumors (such as non-small-cell lung cancer and hypopharyngeal squamous cell carcinoma) [41,42]. Recent studies proved that PLR is related to the prognosis of stroke thrombolysis [43] or endovascular treatment [44].…”
Section: Plos Onementioning
confidence: 99%
“…The PLR was demonstrated to be an independent predictor of diabetes with chronic complications [38][39][40] and tumors (such as non-small-cell lung cancer and hypopharyngeal squamous cell carcinoma) [41,42]. Recent studies proved that PLR is related to the prognosis of stroke thrombolysis [43] or endovascular treatment [44].…”
Section: Plos Onementioning
confidence: 99%
“…Surgical treatment has been identified as an independent factor affecting the prognosis of LUAD patients, presenting a higher survival rate compared with that of non-surgical patients ( 31 ). Furthermore, Shi et al ( 32 ) found that chemotherapy significantly prolonged the survival of patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…TNM stage is widely used in clinical practice for cancer treatment decision-making, while it may limit the clinical usefulness for personalized medicine. 32 , 33 Meanwhile, a single risk factor without any modelling is unable to offer a comprehensive assessment of postoperative outcome. 34 Thus, a statistical model with multiple risk factors is necessary.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Thus, a statistical model with multiple risk factors is necessary. Shi et al 32 constructed a nomogram based on clinical risk factors to predict OS for NSCLC patients, showing a better discrimination ability as well as a better net benefit than the TNM stage alone. In our study, it is worth noting that a TNM stage-based clinical model showed discrimination with lower C-index than did the deep learning signature-based nomogram.…”
Section: Discussionmentioning
confidence: 99%